PTENε suppresses tumor metastasis through regulation of filopodia formation. (23rd March 2021) - Zhang, Qiaoling; Liang, Hui; Zhao, Xuyang; Zheng, Lin; Li, Yunqiao; Gong, Jingjing; Zhu, Yizhang; Jin, Yan; Yin, Yuxin
Abstract: PTEN is one of the most frequently mutated genes in malignancies and acts as a powerful tumor suppressor. Tumorigenesis is involved in multiple and complex processes including initiation, invasion, and metastasis. The complexity of PTEN function is partially attributed to PTEN family members such as PTENα and PTENβ. Here, we report the identification of PTENε (also named as PTEN5), a novel N‐terminal‐extended PTEN isoform that suppresses tumor invasion and metastasis. We show that the translation of PTENε/PTEN5 is initiated from the CUG 816 codon within the 5′UTR region of PTEN mRNA. PTENε/PTEN5 mainly localizes in the cell membrane and physically associates with and dephosphorylates VASP and ACTR2, which govern filopodia formation and cell motility. We found that endogenous depletion of PTENε/PTEN5 promotes filopodia formation and enhances the metastasis capacity of tumor cells. Overall, we identify a new isoform of PTEN with distinct subcellular localization and molecular function compared to the known members of the PTEN family. These findings advance our current understanding of the importance and diversity of PTEN functions. Synopsis: The dual‐specificity phosphatase PTEN has long been appreciated as a pivotal tumor suppressor with complex functions partially attributed to the PTENα and PTENβ family members. This work identifies a novel PTEN isoform designated PTENε (PTEN5), which mainly localizes to the cell membrane and suppresses tumorigenesis by controlling filopodia dynamics. Translation of PTENε is initiated from the CTG816 codon within the 5′UTR of PTEN mRNA. Endogenous expression of PTENε is regulated by eIF2A and a downstream hairpin structure is critical for its alternative initiation. PTENε specifically interacts with cell motility‐related proteins, dephosphorylating VASP at Ser157 or ACTR2 at Thr237/Thr238 sites. Loss of PTENε promotes filopodia formation and tumor metastasis in cell culture and mice, respectively. Abstract : A novel isoform of PTEN is regulated by eIF2A and has a unique function in controlling tumor cell motility.